“Why Do I Need to Come Out if Straight People Don’t Have To?” Divergent Perspectives on the Necessity of Self-Disclosure Among Bisexual Women - Khuzwayo, Zuziwe (Frontiers in Sociology, 2021)
Coming Out has historically been an important, yet often very challenging, process for LGBTQI+ individuals to no longer conceal their sexual and/or gender identity. For those who identify as ‘bisexual’, the process of coming out has proven especially complicated. given that in the general knowledge field of sexuality, bisexuality continues to be a misunderstood, under-researched sexuality and from that negative stigmas and discrimination (even within LGBTQI+ spaces) have contributed to bisexuals not coming out even within the LGBTQI+ community. However, the significance and necessity of coming out itself has come to be questioned, particularly by younger LGBTQI+ people. From a study conducted in Johannesburg, this paper critically considers the different perspectives on coming out of bisexual women. Using a narrative life-history approach through interviews conducted with eight participants, this paper looks at how bisexual women understand the significance of coming out and how this process has different meanings for different age groups. Findings show that there are vastly divergent perspectives, with some participants believing it remains essential, while others argue that the fluidity of their identities no longer requires the same sort of disclosure.